2006
DOI: 10.1136/bjo.2006.107524
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between accommodative amplitude and the ratio of central lens thickness to its equatorial diameter in vertebrate eyes

Abstract: Aim: To determine the relationship between accommodative amplitude and central lens thickness/equatorial lens diameter (CLT/ELD) ratio in vertebrates. Methods: Midsagittal sections of lenses from fixed, post mortem eyes from 125 different vertebrate species were photographed. Their CLT/ELD ratios were correlated with independently published measurements of their accommodative amplitudes. Using the non-linear finite element method (FEM), the efficiency of zonular traction (the absolute change in central radius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The increase in the lens thickness to equatorial diameter ratio shows that the crystalline lens becomes more rounded with age. Across vertebrate species, a flattened lens shape in the unaccommodated state leads to greater change in lens shape with an effort to accommodate (Fisher, 1969;Schachar, Pierscionek, Abolmaali, & Le, 2007). Schachar suggested that lens central thickness to lens equatorial diameter ratio of e0.60 is commonly seen in animals that have the capacity to accommodate (Schachar et al, 2007).…”
Section: Equatorial Lens Diameter and Shapementioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the lens thickness to equatorial diameter ratio shows that the crystalline lens becomes more rounded with age. Across vertebrate species, a flattened lens shape in the unaccommodated state leads to greater change in lens shape with an effort to accommodate (Fisher, 1969;Schachar, Pierscionek, Abolmaali, & Le, 2007). Schachar suggested that lens central thickness to lens equatorial diameter ratio of e0.60 is commonly seen in animals that have the capacity to accommodate (Schachar et al, 2007).…”
Section: Equatorial Lens Diameter and Shapementioning
confidence: 99%
“…Across vertebrate species, a flattened lens shape in the unaccommodated state leads to greater change in lens shape with an effort to accommodate (Fisher, 1969;Schachar, Pierscionek, Abolmaali, & Le, 2007). Schachar suggested that lens central thickness to lens equatorial diameter ratio of e0.60 is commonly seen in animals that have the capacity to accommodate (Schachar et al, 2007). In the current study, while the LT/ED ratio of the crystalline lens increases with age (0.50 at 65 years of age compared to 0.41 at 22 years), it is still within the limits seen for accommodating animal species (i.e., e0.60).…”
Section: Equatorial Lens Diameter and Shapementioning
confidence: 99%
“…[1][2][3] Thickening and anterior positioning of the lens is recognized as a major anatomic predisposing factor for the development of angle closure. 2,4,5 A-scan ultrasonography (A-scan US) and Scheimpflug photography are the techniques commonly used for the LT measurement in vivo.…”
mentioning
confidence: 99%
“…Human and primate lenses have a similar ratio of their central thickness to equatorial diameter after birth, always ⩽0.6 49. Interestingly, animals that have minimal accommodative amplitude—such as mice, dogs, cats, rabbits, goats, sheep, cows, and horses—have lenses with minor axis to major axis ratios greater than 0.6 52 – 56…”
Section: Discussionmentioning
confidence: 99%